Perbandingan Kemampuan Konversi Satuan Panjang Antara Murid yang Memanfaatkan Aplikasi Wordwall di IFP dan Media Tangga Satuan Panjang Interaktif: Sebuah Studi Literatur - Luna Platina; Slamet Arifin; Siti Mas'ula; Riska Pristiani (SAP (Susunan Artikel Pendidikan), 2026)
The ability to perform length unit conversion is a fundamental competency in fourth-grade elementary school mathematics. However, many students still experience difficulties due to learning processes that tend to be procedural and lack the use of media appropriate to their cognitive development stage. This study aims to compare the length unit conversion ability of students who utilize the Wordwall application in the IFP with those who use interactive length unit ladder media based on a literature review. The research method employed is a literature study with a qualitative approach, reviewing ten national and international journal articles published between 2023 and 2025 that are relevant to both learning media. The results indicate that interactive length unit ladder media directly and consistently improves length unit conversion ability, with mastery learning increasing to 81.48% and an N‑Gain score of 0.79 (high category). Meanwhile, the Wordwall application has been proven effective in increasing learning activity and mathematics achievement in general, but it has not been extensively studied specifically on the topic of length unit conversion. These findings highlight the importance of selecting teaching media based on the characteristics of the subject matter and open up opportunities for further experimental research to directly compare the two media in the context of learning unit conversion for length.